(untitled) (Bangladesh Journal of Zoology, 2019)
A study on the phylogenetic relationship of Bangladeshi Skink confirmed species as Eutropis multifasciata by Bayesian inference (BI) (100%) and 98% node support to maximum likelihood (ML) tree topology, respectively. The sequence divergences between Eutropis multifasciata and other congeneric species were significant, ranging from 0.1 to 13.6% for 16S rRNA. Intraspecific genetic divergence within E. multifasciata was estimated 10.3%. E. multifasciata formed a distinct clade with high posterior probability support. This maiden study on Bangladeshi Skink results support that one monophyletic subgroup containing all specimens of E. multifasciata and all recently recognized E. multifasciata populations have evolved from one common ancestor. Bangladesh J. Zool. 47(1): 13-25, 2019